Vegetative Propagation of hibiscus with different types of cuttings and IBA concentrations - Souza, Sra. Rafaela; Beckmann Cavalcante, Márkilla Zunete; Damasceno Lima, Marluce Pereira; Alixandre, Tamnata Ferreira; Nascimento, Rejane Teixeira (Comunicata Scientiae, 2015)
The propagation of the hibiscus is done preferably by cutting. However, the success of this technique depends on the internal and external conditions cuttings, that will influence directly into your rooting capacity. In this sense, the objective was to evaluate the effect of three types of cuttings (apical, middle and basal) and four concentrations of IBA (0, 1000, 3000 and 5000 mg L- 1) in the propagation through cuttings of Hibiscus rosa-sinensisL. cv. Snow Queen. The experiment was conducted in a greenhouse under intermittent mist at the Federal University of Piauí (UFPI), Campus Profa. CinobelinaElvas, Bom Jesus-PI for the period from May 23 to July 7, 2012. The experimental design was completely randomized in a factorial arrangement 3x4 (Type of cuttings x Concentration IBA) with four replications. At 45 days after implantation of the experiment were evaluated: percentage of rooting, survival rate, number of shoots, number of leaves, average root length, dry weight of shoot and root dry weight. There was no significant interaction between the factors studied. There is effective for cutting type. The technique of propagation by cuttings of Hibiscus rosa-sinensis L. cv. Snow Queen is efficient through the use of basal cuttings.